Digital Marketing Strategies in Kazakhstani Super-Apps : A Case Study of Kaspi and Freedom Finance - Talgatuly, Faizolla; Černý, Jan; Potančok, Martin; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This research study explores the digital marketing strategies adopted by the two leading super-apps in Kazakhstan, Kaspi.kz and Freedom Finance, against the backdrop of the digital boom in Kazakhstan. Super-apps affect all financial, e-commerce, and public services into single mobile platforms. Their marketing approaches are thereby gauged against engagement and digital transformation. It is upon earnestly employed methods of data collection, combing academic and industry literature and primary data collected through surveys with marketing and product professionals. The research question therefore consists of two overarching questions: (1) Which marketing strategies are used to support user engagement and retention? (2) What metrics and behaviors are important for fostering 'stickiness' in these apps? Results indicate that Kaspi.kz relies heavily on performing personalization, embedded ecosystem flows, and in-app optimization to keep users frequently in use, while Freedom Finance depends on behavioral segmentation, gamified loyalty systems, and cross-ecosystem promotion to establish long-term relationships with users. Data analytics and emerging technologies like AI fuel both applications, but have clear differences in marketing philosophy. Kaspi emphasizes transactional utility while Freedom builds on emotional engagement and community-building.
Vedoucí práce: Jan Černý
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data and business [obor dipl. práce]; diplomové práce; master's theses